Short-term progestin estrus synchronization with timed insemination for beef heifers: CIDR vs. MGA - Thompson, A.W.; Eborn, D.R.; Keenan, L.D.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Recently, a new product, Eazi-Breed CIDR (a vaginal insert containing progesterone), was approved for estrus synchronization in beef heifers. In previous studies the CIDR has produced excellent estrus synchrony, but it is more costly than the commonly used progestin, melengestrol acetate (MGA). Therefore, the objective of this study was to compare the CIDR to MGA in a shorter-term timed breeding program. Seventy-seven commercial beef replacement heifers were assigned to one of two treatments, CIDR (n=38) or MGA (n=39). Each heifer in the CIDR treatment group received a CIDR on day 1, which was removed on day 7. The MGA treatment group received MGA in the feed each day from day 1 to day 6. All heifers in both treatment groups received an injection of prostaglandin F2α (PGF) on day 7. Forty-eight hours after the PGF injection (day 9), all heifers received an injection of gonadotropin hormone-releasing hormone (GnRH) and were artificially inseminated. Pregnancy status was determined by ultrasonography 29 days post-breeding. A greater percentage (P=0.05) of heifers were pregnant in the CIDR treatment (55%) than in the MGA treatment (33%).
Keywords: Beef; Progestin estrus synchronization; CIDR vs. MGA; Insemination